The anti-inflammatory effects of dexamethasone implants in eyes with heavy silicone oil: a prospective study on vitrectomy for diabetic retinopathy - Zhang, Xingguo; Dong, Junliang; Lu, Haomin; Sun, Minghao; Xu, Shuning; Zhang, Yuege; Peng, Yi; Sun, Dawei; Jiang, Bo (Frontiers in Endocrinology, 2025)
PurposeThis study aims to assess the effects of heavy silicone oil (HSO) tamponade in patients with diabetic tractional retinal detachment (TRD) treated with pars plana vitrectomy (PPV), and to evaluate the role of extended-release hormone implantation in controlling inflammation and mitigating postoperative complications.MethodsA prospective, randomized, controlled design was used in this study. This study included 96 eyes from 96 patients diagnosed with diabetic TRD, all of whom were treated at our institution between March 2024 and March 2025. Group 1 consisted of 54 eyes from 54 patients (PPV + HSO + dexamethasone implant), while Group 2 included 42 eyes from 42 patients (PPV + HSO). The primary outcomes included best-corrected visual acuity (BCVA), intraocular pressure (IOP), retinal reattachment rate, anterior chamber (AC) fibrin exudation, anterior proliferative vitreoretinopathy (PVR), and posterior iris synechiae during the 3-month postoperative follow-up period.ResultsEighty eyes from 80 patients were ultimately included in the study, with 40 eyes assigned to each group. Patient characteristics, including age, sex, preoperative HbA1c levels and preoperative blood pressure,DR severity were similar (P >0.05). Both groups demonstrated improvements in BCVA postoperatively compared to baseline (P <0.05,Bonferroni adjusted). Group 1 demonstrated a improvement in BCVA compared to Group 2 at 1 month and 3 months postoperatively,but P >0.05 after adjusted. At 3 months postoperatively, IOP did not differ significantly between the groups (P > 0.05). At 1 week postoperatively, AC fibrin exudation was decreased in Group 1(P = 0.007, P = 0.07 Bonferroni adjusted). At 3 months postoperatively,compared with Group 2, Group 1 had significantly lower postoperative anterior PVR (P = 0.010 Bonferroni adjusted), Group 1 had lower rates of retinal reattachment and posterior iris synechiae (P = 0.032 and P = 0.008, all P>0.05 Bonferroni adjusted).ConclusionTo our knowledge, this first study of dexamethasone implants with HSO in PDR suggests intraoperative DEX may be a safe, potentially beneficial adjunct for diabetic TRD undergoing phacoemulsification plus vitrectomy with HSO, reducing inflammation and number of anti-VEGF injections over 3 months, and offering useful directions for future research in this preliminary prospective evaluation overall.